GENERALIZED CHYLOUS PERITONITIS: A CASE REPORT - S. N. Styazhkina; A. A. Akimov; A. A. Abramovich; E. Yu. Belova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Peritonitis is the most common complication in abdominal surgery. The outcomes of peritonitis may vary from complete recovery to death, depending on time to diagnosis and treatment strategy. Therefore, the doctor has to know early clinical signs and patterns of this disease in order to ensure a favorable outcome of the disease and rapid recovery of the patient. In this article, we report a case of generalized chylous peritonitis (with identified cause) in a 59- year old female patient treated in the First Republican Clinical Hospital, Ministry of Health of the Udmurt Republic.